1985
DOI: 10.1007/bf01310965
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of tyrosine hydroxylase activity in PC12 cells infected with herpes simplex virus type 1

Abstract: During infection with herpes simplex virus type 1 (HSV-1) the activity of tyrosine hydroxylase (TH) in PC12 pheochromocytoma cells was initially depressed reaching a nadir at 6 hours post-inoculation, but recovered rapidly with a return to baseline activity by 8 to 9 hours post-inoculation. Subsequently, TH activity again fell with a second more variable rise in activity occurring at 24 hours post-inoculation. Studies with metabolic inhibitors and 2 temperature-sensitive viral mutants indicated that these alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Infection by Herpes simplex virus type I has been reported to depress tyrosine hydroxylase activity in PC12 (Rubenstein et al, 1985). We have found that, in at least five of the six HPRT-deficient variants, transformation with HPRT retrovirus had no adverse effects on dopamine metabolism.…”
Section: And Their H P R T -C O N T a I N I N G Derivatives O B T A Imentioning
confidence: 67%
“…Infection by Herpes simplex virus type I has been reported to depress tyrosine hydroxylase activity in PC12 (Rubenstein et al, 1985). We have found that, in at least five of the six HPRT-deficient variants, transformation with HPRT retrovirus had no adverse effects on dopamine metabolism.…”
Section: And Their H P R T -C O N T a I N I N G Derivatives O B T A Imentioning
confidence: 67%
“…These cells can be induced to undergo morphological and physiological differentiation, characterized by a lack of cell division, extension of functional processes, and expression of a variety of neuronal cell-specific markers, following exposure to low doses of nerve growth factor (NGF) (25,26). It has been previously reported that NGF differentiation of PC12 cells persistently infected with herpes simplex virus (HSV) type I delays the transition from early to late HSV polypeptide synthesis (13), while other groups have shown that HSV infection of differentiated PC12 cells leads to transient decreases in levels of enzymes involved in acetylcholine metabolism (54,55).…”
mentioning
confidence: 99%